Frank Lloyd Wright vision and legacy. - Selby, Robert I.; Committee of Architectural Heritage (Illinois : University of Illinois, 1966)
tentoonstelling met nadruk op "the Robie House"
Adlib record nr. 530002748
boek
Keywords: Wright, Frank Lloyd; modernisme; Verenigde Staten van Amerika